Pengaruh Kualitas Pelayanan, Harga dan Cita Rasa terhadap Kepuasan Pelanggan pada Rumah Makan Mekar Sari di Kabupaten Trenggalek - Gilang Permata; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
Mekar Sari Restaurant is a culinary business with a fresh vegetables menu that is much sought after by the people of Trenggalek Regency. Many competitors have emerged with similar businesses and menus, so it is necessary to implement special strategies to be able to win the competition and attract customer visits so that they can make large sales. Based on previous research, customer satisfaction has been proven to be effective in influencing buyer interest. The factors that influence customer satisfaction are good service quality, affordable prices, taste according to the customer's tongue. This research aims to determine the influence of service quality, price and taste on customer satisfaction at RM. Mekar Sari. The population used in this research is customers who have purchased at RM. Mekar Sari. This research uses a quantitative approach with an associative type. The sampling technique in this research used accidental sampling technique. The sample size calculation uses the Lemeshow formula at a confidence level of 10% to obtain a sample size of 100 respondents. Data collection was carried out using a questionnaire. The analysis method uses multiple linear regression analysis with the help of the SPSS version 26 program. Hypothesis testing uses the simultaneous f test and partial t test. The results of this research show that service quality, price and taste simultaneously have a positive and significant effect on customer satisfaction. Partially, service quality, price and taste also have a positive and significant effect on customer satisfaction.